2007
DOI: 10.1016/j.jhse.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Treatment of Cubital Tunnel Syndrome: A Decision Analysis

Abstract: The objective of our study was to use decision analysis to compare four common surgical treatments for cubital tunnel syndrome: simple decompression of the cubital tunnel, medial epicondylectomy, anterior subcutaneous transposition and anterior submuscular transposition. The variables used for this decision analysis model were based on data from the literature. Extensive sensitivity analyses were carried out to test the impact of the values given to these variables on the outcome of the model. The highest expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 56 publications
(91 reference statements)
0
21
0
1
Order By: Relevance
“…One study examined utility scores for each procedure. 20 Overall, simple decompression was found to have the highest utility, and a cost analysis study also found it to be less expensive than subcutaneous transposition. 16 …”
Section: Analysis Of Results By Outcomes Measurementioning
confidence: 98%
“…One study examined utility scores for each procedure. 20 Overall, simple decompression was found to have the highest utility, and a cost analysis study also found it to be less expensive than subcutaneous transposition. 16 …”
Section: Analysis Of Results By Outcomes Measurementioning
confidence: 98%
“…4,5 This is supported by a detailed decision analysis model that favors in situ decompression. 21 With the acceptance of in situ decompression as an effective treatment for cubital tunnel syndrome, methods for minimally invasive 22 and endoscopic-assisted ulnar nerve decompression have been investigated. A technique for endoscopic in situ decompression was first described by Tsai et al 9 Subsequently, alternative techniques have been described, 7,8,10,23 with supporting anatomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…The only clinical decision-analysis study with a reliable design recommends simple decompression as the preferred surgical treatment for moderate-to-severe cubital tunnel syndrome, with submuscular transposition as a salvage procedure if sensory symptoms are not resolved [5]. Some assumptions are necessary for the creation of such study, based on probability of occurrences of both the utilities (favorable advantages) and the disutilities (complications or inconveniences) of the different procedures.…”
Section: Resultsmentioning
confidence: 99%